Tank Mixtures of Vida for Late Summer Weed Control in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Kochia control at soon after application was best when Vida (pyraflufen) was tank mixed with glyphosate, 2,4-D amine, and/or dicamba. However, no Vida treatment controlled kochia more than 60% one month after treatment. Treatments containing glyphosate, 2,4-D, and/or dicamba without Vida did not control kochia more than 33% during the first month. Similarly, Russian thistle control was best regardless of evaluation date when Vida was applied alone or tank mixed with another herbicide. Vida treatments provided 90 to 94% Russian thistle control one month after treatment. Treatments without Vida controlled Russian thistle no more than 63%.
Keywords: Late postemergence